Chemical Compositions of the Essential Oils of Different Stages of the Growth of Stachys inflata Benth. from Iran - HADI MESHKATALSADAT, MOHAMMAD; PIRAEI, MARZIEH; AMIRI, HAMZEH (Asian Journal of Chemistry, 2010)
The chemical compositions of a hydrodistilled oils of different stages of growth Stachys inflata Benth. Growing wild in Iran was examined by GC and GC/MS. The major components of the oils were germacrene-D (pre-f. 30.3 %, f. 12.38 % and post-f. 32.9 %), bicyclogermacrene (pre-f 3.49 % f. 11.26 %, post-f. 7.3 %), α-pinene (pre-f. 18.48 % f. 9.11 %, post-f. 2.6 %), limonene (pre-f. 16.41 % f. 11.14, post-f. 15.6 %), α-pinene (pre-f. 9.756 % f. 4.54 % post-f. 2.5 %) and spathulenol (pre-f. 3.2 %, f. 13.56 %, post-f. 7.5 %) (f - flowering).